Prostaglandin F2α and GnRH administration improvedprogesterone status, luteal number, and proportionof ovular and anovular dairy cows with corpora luteabefore a timed artificial insemination program - Stephanie Leeann Pulley; H.I. Jr. Mellieon; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2011)
The objective of this research was to increase the proportion of cows with at least 1 functional corpus luteum (CL) and elevated progesterone at the onset of the timed artificial insemination (TAI) program. Postpartum Holstein cows in 1 herd were stratified by lactation number at calving (September 2009 through August 2010) and assigned randomly to 1 of 2 treatments: (1) Presynch-10 (n = 105): two 25-mg injections of prostaglandin F2α(PG) 14 days apart (Presynch); and (2) PG-3-G (n = 105): one 25-mg injection of PG 3 days before 100 Î¼g gonadotropin- releasing hormone (GnRH; Pre-GnRH), with the PG injection administered at the same time as the second PG in the Presynch-10 treatment. Cows were enrolled in a TAI protocol (Ovsynch; injection of GnRH 7 days before [GnRH-1] and 56 hours after [GnRH-2] PG with AI 16 to 18 hours after GnRH-2) 10 days after the second or only PG injection. Blood samples for progesterone or estradiol analyses were collected on median days in milk (DIM): 36, 39, 50, 53 (Pre-GnRH), 60 (GnRH-1), 67 (PG), 69 (GnRH-2), and 70 (TAI). Ovarian structures were measured by ultrasonography on median DIM 53, 60, 67, 69, and 6 days post-TAI to determine follicle diameters, ovulation response to GnRH, or both. Although progesterone concentration did not differ between treatments before Pre-GnRH injection, the proportion of cows with at least 1 CL tended to be greater for PG-3-G than Presynch-10 cows, and more PG- 3-G cows ovulated after Pre-GnRH than ovulated spontaneously in Presynch-10. Furthermore, diameter of follicles that ovulated tended to be smaller in PG-3-G than Presynch-10 cows after Pre-GnRH. At GnRH-1, the proportion of cows with progesterone ≥1 ng/mL, the number of CL per cow, and the proportion of cows with at least 1 CL were greater for PG-3-G than Presynch-10. Neither follicle diameter nor percentage of cows ovulating after GnRH-1 differed between treatments. At PG injection during the week of TAI, progesterone concentration and the proportion of cows with progesterone ≥1 ng/mL tended to be greater for PG-3-G than Presynch-10, and PG-3-G had more CL per cow than Presynch-10. No ovarian characteristics differed between treatments after GnRH-2, including progesterone concentration, number of CL per cow, and total luteal volume 7 days after GnRH-2. Many of the previous ovarian traits were improved in both ovular and anovular cows after PG- 3-G compared with Presynch-10. Pregnancies per AI at days 32 and 60 were only numerically greater for PG-3-G vs. Presynch-10 cows, largely because of differences detected during months without heat stress. We concluded that the PG-3-G treatment increased ovulation rate and luteal function 7 days before the onset of Ovsynch, resulting in improved follicular synchrony and predisposing potentially greater pregnancies per AI in lactating dairy cows.; Dairy Day, 2011, Kansas State University, Manhattan, KS, 2011; Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-176-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1057; Dairy; Luteal function; Ovulation; Presynchronization; Progesterone; Timed artificial insemination (TAI)